Long‐Term Mean Mass, Heat and Nutrient Flux Through the Indonesian Seas, Based on the Tritium Inventory in the Pacific and Indian Oceans. Issue 6 (17th June 2019) - Xie, Tengxiang; Newton, Robert; Schlosser, Peter; Du, Chuanjun; Dai, Minhan
Abstract: The Indonesian Throughflow (ITF), the only oceanic tropical pathway linking the Pacific and Indian Oceans, plays a critical role in the redistribution of heat and mass, affecting both the regional and global climate systems. Based on the distributions and changes in the tritium inventories, and tritium budgets in and between the South Pacific and South Indian Oceans from the Geochemical Ocean Sections Study and World Ocean Circulation Experiment programs, the long‐term mean water mass transport of the ITF is estimated. The total throughflow of the ITF is estimated as 16.2 ± 3.5 Sv. The North Pacific contributes 14.1 ± 2.7 Sv to the total throughflow, of which the layers between 0–250, 250–650, and 650–1, 000 m carry 7.3 ± 0.6, 5.4 ± 1.3, and 1.4 ± 3.0 Sv, respectively. Along with the water transport, the North Pacific component of the ITF transfers 0.84 ± 0.14 PW of heat into the Indian Ocean, of which almost 90% exits from the Indian Ocean at 30°S. The net nitrate flux into the photic zone associated with the ITF is 2.71 ± 2.60 mmol·m −2 ·d −1 in the Indonesian Seas, ~90% of which is induced by vertical diffusion. Plain Language Summary: The water transfer between the Pacific and Indian Oceans, commonly referred to as the Indonesian Throughflow (ITF), is the only tropical interbasin oceanic pathway, which plays a critical role in the redistribution of heat and mass, affecting both the regional and global climate systems. Due to the strong variability at both seasonal and interannual‐interdecadal timescales and the multipathway of the ITF, constraining the long‐term mean ITF volume transport is challenging. Chemical tracer method is a good complement for physical observations to constrain the temporally integrated result. In this work, we use tritium data from Geochemical Ocean Sections Study and World Ocean Circulation Experiment to quantify the long‐term averaged volume transport of the ITF based on the difference in tritium inventory between the South Indian Ocean and the South Pacific Ocean. The total throughflow of the ITF is estimated as 16.2 ± 3.5 Sv. Along with the water transport, the North Pacific component of the ITF transfers 0.84 ± 0.14 PW of heat into the Indian Ocean, of which almost 90% exits from the Indian Ocean at 30°S. The net nitrate flux into the photic zone associated with the ITF is 2.71 ± 2.60 mmol·m −2 d −1 in the Indonesian Seas, 90% of which is induced by vertical diffusion. Key Points: The total long‐term mean water transport of the ITF is 16.2 ± 3.5 Sv derived from tritium budgets in the South Pacific and South Indian Oceans The North Pacific component of the ITF transfers 0.84 ± 0.14 PW heat into the Indian Ocean Vertical diffusion dominates nutrient supply to the photic zone in the Indonesian Seas